Uma Escola Chamada Salazar? - PIMENTEL, Jorge Cunha (2012)
From the late 1920’s and throughout the 1930’s Rogério de Azevedo carried on two apparently conflicting careers simultaneously accepting private commissions (mostly in Oporto) and public works (in Northern and Central Portugal). Astride the generations of Marques da Silva, his teacher, and Januário Godinho, a trainee at the time taking part in various projects at Rogério de Azevedo’s offices, his work developed through various programmes in which the sense for the site is never irrelevant and the architectonic object is never indisputably autonomous; it is a process of free interpretation reconciling modernity and tradition, linked together around the site and its history, and refusing to accept a nationalistic manner.